HUBUNGAN KELENTURAN PERGELANGAN TANGAN DENGAN HASIL PASSING ATAS PADA TIM BOLA VOLI PUTRI JURUSAN PENDIDIKAN OLAHRAGA UNIVERSITAS RIAU - ', Suherman; ', Slamet; ', Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research was conducted by using correlational research design which aims to investigate how far the relationship between the flexibility of the wrist with passing results on the population of women's volleyball team majoring in Physical Education Pekanbaru , Riau University consisting of 16 persons . The sampling technique in this research is total sampling technique . Because the population is less than or less than 100 people , then a sample is taken from the sum of all the existing population that numbered 16 people . Instruments used to collect data in this research is to use measurements of variables contained in this research that tests the flexibility of the wrist by using the maximum degree ( Flexy Maeseures ) and passing tests on additionally , analisisis statistical data , normality test done Liliefours test at a significance level Î± = 0.05 . Based on the results of research conducted , which test the normality of the data obtained Lo ( X ) 0.1173 while Lo ( Y ) 0.1444 and Ltable = 0.213 so if Lomaks< Ltable then the data is normally distributed. From the calculation of the Pearson product moment correlation variable x to y obtained rcount = 0.91 < of rtable so Ha is accepted and Ho rejected. Conclusion The hypothesis of this study was accepted hypothesis at a significance level = 0.05, in other words there is a significant relationship between the flexibility of the wrist with passing results in women 's volleyball team from the Department of Physical Education , University of Riau.Keywords : Flexibility of the wrist , passing over